Generating Photomosaics with QR Code Capability - Chin-Lin Li; Yangcong Su; Ran-Zan Wang (Mathematics, 2020)
A photomosaic is an image with two layers of visual information, including an overarching image that can be seen from a distance and a matrix of individual tile images when examined closely. This paper presents a method for generating photomosaics with an additional layer of quick response code (QR code) information that can be accessed by typical QR code scanners in cell phones. The basic idea is to carefully classify the tile images in different categories and generate the photomosaic patches by referring to the properties of QR code modules. Three levels of construction methods for generating the proposed photomosaics in different image resolutions are proposed. The results show that the generated photomosaics have good visual quality and high robustness for decoding the QR code. The proposed method endows conventional photomosaics with the QR code capability. It extends photomosaics from exhibiting purely visual information to the linkage of multimedia data. Furthermore, it increases the feasibility and potential of applying photomosaics in diverse applications, such as activity promotions or commercial product advertisements.